Enhancement of the Antibacterial Efficiency of Silver Nanoparticles against Gram-Positive and Gram-Negative Bacteria Using Blue Laser Light - Anes Al-Sharqi; Kasing Apun; Micky Vincent; Devagi Kanakaraju; Lesley Maurice Bilung (International Journal of Photoenergy)
Silver nanoparticles (Ag-NPs) possess excellent antibacterial properties and are considered to be an alternative material for treating antibiotic-resistant bacteria. The present study was aimed at enhancing the antibacterial efficiency of Ag-NPs using visible laser light against Escherichia coli and Staphylococcus aureus in vitro. Four concentrations of Ag-NPs (12.5, 25, 50, and 100 μg/ml), synthesized by the chemical reduction method, were utilized to conduct the antibacterial activity of prepared Ag-NPs. The antibacterial efficiencies of photoactivated Ag-NPs against both bacteria were determined by survival assay after exposure to laser irradiation. The mechanism of interactions between Ag-NPs and the bacterial cell membranes was then evaluated via scanning electron microscopy (SEM) and reactive oxygen species analysis to study the cytotoxic action of photoactivated Ag-NPs against both bacterial species. Results showed that the laser-activated Ag-NP treatment reduced the surviving population to 14% of the control in the E. coli population, while the survival in the S. aureus population was reduced to 28% of the control upon 10 min exposure time at the concentration of 50 μg/ml. However, S. aureus showed lower sensitivity after photoactivation compared to E. coli. Moreover, the effects depended on the concentration of Ag-NPs and exposure time to laser light. SEM images of treated bacterial cells indicated that substantial morphological changes occurred in cell membranes after treatment. The results suggested that Ag-NPs in the presence of visible light exhibit strong antibacterial activity which could be used to inactivate harmful and pathogenic microorganisms.